Analysis of problems in building ventilation energy-saving design. Issue 1 (January 2021) - Wang, Shouchuan; Li, Siwen; Zhou, Yuwen; Ge, Tan; Wang, Xiaoguang
Abstract: With the development of modern science and technology, the work of all walks of life has been further improved, and related content has become more abundant. Building construction is a problem that people attach great importance to now. Only by better grasping the relevant content, developing the core strength, and improving the strength of the enterprise can practical problems be effectively solved. Building ventilation and energy-saving design is one of the important aspects. The problems in the ventilation design are handled well, the analysis is carried out accurately, and effective solutions are grasped to ensure the quality of the design, so as to play an active role in the development.